Squamous Cell Carcinoma Hallmark and Treatment Modalities - Elia Daaboul, Hamid (IntechOpen, 2020)
With the support of multinational specialists, each with different background and separate field of expertise in oncology, this book had the occasion to emerge and to offer physicians, researchers and academics efficient, well-organized and updated scientific information related to the characteristics and treatment modalities of squamous cell carcinoma. It provided in-depth information regarding the comprehension of the molecular interaction of signalling pathways and new phenotypes that might result and lead to further cell proliferation and metastases. It also emphasized on the management and individualization of treatment strategies in different types of SCC, applying molecular profiling and approved protocols in order to identify new treatment opportunities. This book also discussed the potential therapeutic modalities that might arise upon understanding and exploring the role of key regulatory proteins that govern the process of cutaneous SCC progression. And Lastly, it underlined the molecular aberrations present in SCC of different organs and the possibility of emerging new therapeutic drugs by targeting these abnormalities. It is really an innovative record that combined novel information from various medical sources and mixed it to become unified in its scientific profit.